Double cup love : on the trail of family, food, and broken hearts in China - Huang, Eddie, 1982- (Spiegel & Grau, 2016)
"As he entered adulthood (of sorts), Huang began to wonder just how authentic his Chinese identity really was, a dilemma that grew more acute as he contemplated proposing marriage to his all-American (well, all-Italian-American) girlfriend. So he enlisted his brothers Emery and Evan and returned to the land his ancestors had abandoned. His immediate goal was to sample the best food in China, from four-star restaurants in Shanghai to sidewalk vendors in Chengdu, and open his own stand to see if his food stood up to Chinese tastes--but his deeper goal was to reconnect with his homeland, repair his frayed family relationships, decide whether to marry to his American girlfriend, and figure out just where to find meaning in his life."--Provided by publisher.